2006
DOI: 10.1186/bf03352670
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of static stress drops for aftershocks of the 2005 West Off Fukuoka Prefecture earthquake

Abstract: We investigated the spatial distribution of static stress drops of the aftershocks of the 2005 West Off Fukuoka Prefecture earthquake, with the aim of assessing the possibility that another earthquake will occur on the SE extension of the earthquake fault. The waveforms from six temporary online telemetry stations installed in and around the aftershock region were measured. Small stress drops were estimated for the aftershocks that occurred relatively distant from the SE and NE ends of the earthquake fault. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…For both P-and S-wave analyses, all the estimations of static stress drops are averaged across all stations available. These values approximately coincide with the estimated static stress drops of aftershocks of other inland earthquakes in Japan (Ito 2005;Iio et al 2006), although the estimation procedures used differ from those used in this study. Figure 3 shows a relationship between the local magnitude of the analyzed earthquake and the estimated static stress drop of the average case.…”
Section: Resultssupporting
confidence: 68%
“…For both P-and S-wave analyses, all the estimations of static stress drops are averaged across all stations available. These values approximately coincide with the estimated static stress drops of aftershocks of other inland earthquakes in Japan (Ito 2005;Iio et al 2006), although the estimation procedures used differ from those used in this study. Figure 3 shows a relationship between the local magnitude of the analyzed earthquake and the estimated static stress drop of the average case.…”
Section: Resultssupporting
confidence: 68%
“…We consider a body with many earthquakes in ΔV, which is deformed by earthquake faulting that behaves as a volumetric source in the media surrounding ΔV. Moment tensors distributed in the volume express the inelastic deformation (Aki and Richards 1980;Ichihara et al 2016;Kusakabe et al 2016), and the relationship between inelastic strain ε p ij in the volume and the moment density tensor may be expressed using the compliance C ijkl of the volume (Noda and Matsu'ura 2010): Iio et al (2006) and the CMT catalog by NIED. Orange ovals represent the average moment value for each magnitude range at intervals of 0.2.…”
Section: Seismogenic Zone Strain Inferred From Seismic Momentsmentioning
confidence: 99%
“…The method used in this study requires information regarding the magnitude of seismic moment tensors in addition to focal mechanisms. Matsumoto (2016) adopted seismic moment (M 0 ) data by Iio et al (2006) and the moment tensor (MT) solution catalog from the National Institute of Earth Science and Disaster Resilience (NIED). For events not found in the moment tensor magnitude dataset, scalar seismic moments were inferred from empirical relationships between the scalar moment and magnitude estimated short-period velocity seismogram (M a ) as shown in Fig.…”
Section: Inelastic Strain In Kyushu Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their analyses of hypocenter location, focal mechanism solutions, Coulomb failure stress, and stress tensor inversion, they showed that the off-fault earthquakes were the reactivation of a structural boundary. Iio et al (2006) estimated the spatial distribution of static stress drops of the aftershocks and concluded that off-fault aftershocks were generated on very weak pre-existing fault planes based on the finding that stress drops of the off-fault earthquake were relatively small. On the other hand, the stress drops of the aftershocks occurring at the SE end of the aftershock region were large.…”
mentioning
confidence: 99%